2019
DOI: 10.1039/c8fo01892h
|View full text |Cite
|
Sign up to set email alerts
|

Liquid state fermentation vinegar enriched with catechin as an antiglycative food product

Abstract: Catechin, a natural antiglycative agent, was incorporated into fermented vinegar, and has high potential to lower the risk of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…For instance, green tea catechins can be used in nutraceuticals for body-weight management [ 21 ]. Wu et al [ 22 ] reported that catechin incorporated into fermented vinegar may lower the risk of diabetes, which was due to its strong inhibition of the diabetes-related metabolic enzymes. Therefore, catechins can exert their nutritional and health value by inhibiting the activity of some disease-related enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, green tea catechins can be used in nutraceuticals for body-weight management [ 21 ]. Wu et al [ 22 ] reported that catechin incorporated into fermented vinegar may lower the risk of diabetes, which was due to its strong inhibition of the diabetes-related metabolic enzymes. Therefore, catechins can exert their nutritional and health value by inhibiting the activity of some disease-related enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…LSF has a short fermentation time, high yield and low cost compared with SSF (Wu et al, 2019). Of the above four kinds of vinegar, only FYMV uses LSF, while others use SSF (Chen et al, 2019). Due to the diversity of raw materials and production technology of vinegar, the characteristic aroma substances of vinegars from different producing areas and brands are very different.…”
Section: Introductionmentioning
confidence: 99%
“…LSF is microbial cultures grown on a system with high water content (Zieliński et al., 2019). LSF has a short fermentation time, high yield and low cost compared with SSF (Wu et al, 2019). Of the above four kinds of vinegar, only FYMV uses LSF, while others use SSF (Chen et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Humans are exposed to AGEs in two ways, via endogenous AGEs generated from abnormal glucose metabolism or lipid peroxidation or via exogenous AGEs from various foods that they consume daily. Exogenous AGEs can enter the bloodstream and grow in the body ( 4 ). The AGEs accumulated in the body can increase oxidative stress, activate nuclear factor-κB, further inducing various cytokines and growth factors.…”
Section: Introductionmentioning
confidence: 99%